CORRELATION BETWEEN MOTIVATI ON AND ATTITUDE TOWARD EFL LEARNING: A STUDY OF UNDERGRADUATE STUDENTS AT STUDY PROGRAM OF ENGLISH UNIVERSITAS BRAWIJAYA - PRAMINATIH, GUSTI AYU (Jurnal Ilmiah Mahasiswa FIB, 2015)
Keywords: affective factor, motivation, attitude.Foreign language such as English is barely spoken by the people outside English-speaking countries. Therefore, to master the language, English learners should give emphasize on two most important factors that influence their achievement in learning the language. The factors are motivation and attitude. The writer conducted a study about first year undergraduate students’motivation and attitude and also correlation between those two variables. There are three problems of the study namely: (1) What degree of motivation owned by first year undergraduate students of Study Program of English Universitas Brawijaya; (2) What degree of attitude owned by first year undergraduate students of Study Program of English Universitas Brawijaya; and (3) What is the correlation between motivation and attitude owned by first year undergraduate students of Study Program of English Universitas Brawijaya.This study used descriptive quantitative approach because the data being analyzed was in the form of statistical data. The data were obtained from Attitude Motivation Test Battery (AMTB) questionnaire from 119 participants.In this study, the writer found that first year undergraduate students of Study Program of English Universitas Brawijaya were both integratively and instrumentally motivated. They also have positive attitude toward learning English and attitude toward English-speaking people. And there was a strong correlation between motivation and attitude.The writer suggests first year undergraduate students to interact more with English native speakers and also take courses that have practical purposes. For the lecturers, they are suggested to design teaching and learning activities in accordance with the students’needs. Finally, future researchers are expected to conduct research about motivation and attitude or any other affective factors in different approach.